A thiol-modified MOF material, a synthesis method and applications thereof
Patent Information
- Application Number
- CN202410916483.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-07-09
AI Technical Summary
Smart Images

Figure CN118745255B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heavy metal pollutant treatment technology, and more specifically, relates to a mercapto-modified MOF material, its synthesis method, and its application. Background Technology
[0002] With industrial development, the discharge of wastewater containing heavy metal pollutants has been increasing. Currently, the main treatment methods for heavy metal pollutants are chemical precipitation and adsorption. Chemical precipitation is relatively inexpensive because heavy metals are generally easily hydrolyzed; adding lime, soda ash, etc., can convert heavy metal pollutants into precipitates. However, excessive addition can easily generate alkaline byproducts, the precipitation rate is limited by the chemical equilibrium constant, and the resulting precipitated sludge often contains multiple components, making it only suitable for hazardous waste disposal and difficult to reuse.
[0003] Unlike chemical precipitation, adsorption methods use specialized adsorbents to adsorb heavy metal ions. Adsorption methods are classified into four types: flocculation, physical adsorption, chemical adsorption, and ion exchange. Flocculation uses flocculants to convert heavy metal ions into flocculent precipitates for removal; it is highly efficient and low-cost, allowing for the precipitation of large quantities of heavy metal ions with a small amount of flocculant. Physical adsorption uses adsorbents with high specific surface area, such as activated carbon, for direct adsorption. However, physical adsorption has a low average adsorption capacity and lacks selectivity; in water, its adsorption capacity is rapidly occupied by water molecules, generally limiting its application to gas purification. Ion exchange utilizes a metathesis reaction between ion exchange resins and heavy metal ions on the solid phase. With proper design, it can effectively and selectively separate heavy metal ions from aqueous solutions and can desorb through regeneration. However, ions loaded in the ion exchange resin, such as sodium, potassium, and ammonium, can also enter the water, potentially increasing the salt concentration. Chemical adsorption generally uses materials containing specific functional groups that form coordination bonds with ions, transferring them from the water to the adsorbent material. Similar to ion exchange resins, chemical adsorption also has good selective adsorption performance, and it does not release ions into the water during the adsorption process, resulting in relatively less pollution to water bodies.
[0004] UiO-66 is a metal-organic framework (MOF) composed of metal ions and organic ligands. It typically possesses a highly ordered porous structure, which makes UiO-66 widely applicable in gas adsorption, separation, storage, and catalysis. Specifically, UiO-66 is a rigid metal-organic framework material with Zr as the metal center and terephthalic acid (H₂BDC) as the organic ligand, exhibiting excellent hydrothermal and chemical stability. Its crystal structure remains stable at 500 °C, and the framework structure can withstand mechanical pressure of 1.0 MPa. UiO-66 maintains structural stability in solutions such as water, DMF (N,N-dimethylformamide), benzene, or acetone, and also exhibits strong acid and alkali resistance.
[0005] Based on the theory of hard and soft acids and bases, the adsorption capacity of the same functional group for different ions is directly related to its hardness. Soft bases, such as thiols, thioethers, and isocyanates, have a stronger ability to coordinate with soft acids, while hard bases, such as carboxylic acids, alcohols, and amines, have a stronger ability to coordinate with hard acids. Heavy metal pollutants include both hard and soft acids and bases, but those with greater hazards, such as lead, cadmium, mercury, and thallium, are all soft acids, with lead emissions being particularly high. Theoretically, using adsorbents containing thiol groups can effectively remove lead ions from water.
[0006] Currently, there are many materials capable of loading thiol groups onto their surfaces. Among them, metal-organic frameworks (MOFs) have become a research hotspot due to their advantages of large specific surface area, stable properties, and simple preparation. Using MOFs as carriers for surface-loaded thiol materials can leverage their large surface area to achieve high adsorption capacity and significantly improve adsorption efficiency.
[0007] Chinese patent CN109317104A, applied for by Beijing University of Technology, discloses a thiol-functionalized metal-organic framework UiO-66-SH. First, zirconium chloride, 2-aminoterephthalic acid, and N,N-dimethylformamide solution were reacted under concentrated hydrochloric acid conditions to prepare UiO-66-NH2. Then, UiO-66-NH2 was reacted with mercaptoacetaldehyde to prepare a new functional material. Compared to UiO-66-NH2, this new material exhibits a maximum adsorption capacity of 490.98 mg / g for mercury ions. However, this material is only suitable for adsorbing mercury ions and cannot be used for adsorbing lead ions.
[0008] Currently, there are no reported patent studies on the application of UiO-66 type metal-organic framework-supported thiol adsorbent materials in the adsorption of lead ions. Summary of the Invention
[0009] To address the shortcomings and drawbacks of the existing technology, the first aspect of the present invention provides a mercapto-modified MOF material, characterized in that it comprises the structure of formula (I) below. (I), where Represents UiO-66; R represents or .
[0010] The second aspect of the present invention provides a method for synthesizing the thiol-modified MOF material described in the first aspect of the present invention, comprising the following steps: 1) reacting a zirconium-based organometallic framework precursor with an aldehyde to obtain an aldehyde-modified metal-organic framework; 2) reacting the aldehyde-modified metal-organic framework with a thiol monomer to obtain the thiol-modified MOF material.
[0011] Preferably, the zirconium-based organometallic framework precursor is UiO-66-NH2. The aldehyde is glutaraldehyde, and the aldehyde-modified metal-organic framework is UiO-66-CHO. The thiol monomer is trithiocyanate or 2,5-dimercapto-1,3,4-thiadiazole.
[0012] Preferably, the solvent used in step 1) is selected from one or more of methanol, ethanol, acetone, THF or DMF.
[0013] Preferably, the solvent used in step 1) is selected from ethanol.
[0014] Preferably, the reaction temperature in step 1) is selected from 50~150℃.
[0015] More preferably, the reaction temperature in step 1) is selected from 50~80℃.
[0016] Preferably, the reaction time in step 1) is selected from 12 to 36 hours.
[0017] More preferably, the reaction time in step 1) is selected from 12 to 24 hours.
[0018] Preferably, the mass ratio of the zirconium-based organometallic framework precursor to the aldehyde is (1~5):(1~10). More preferably, the mass ratio of the zirconium-based organometallic framework precursor to the aldehyde is (4~5):(5~10).
[0019] Most preferably, the mass ratio of the zirconium-based organometallic framework precursor to the aldehyde is (4~5):10.
[0020] Preferably, the aldehyde enters the reaction in the form of an aqueous solution.
[0021] Preferably, the aldehyde concentration is 50%.
[0022] Preferably, after the reaction in step 1) is completed, the product is post-processed.
[0023] Preferably, the post-processing includes filtration, separation, washing, and drying.
[0024] Preferably, the washing includes washing once or multiple times with ethanol and / or water.
[0025] Preferably, the solvent used in step 2) is selected from one or more of DMF, 1,4-dioxane or DMSO.
[0026] More preferably, the solvent used in step 2) is selected from DMF.
[0027] Preferably, the reaction temperature in step 2) is selected from 50~240℃.
[0028] More preferably, the reaction temperature in step 2) is selected from 80~120℃.
[0029] Preferably, the reaction time in step 2) is selected from 12 to 36 hours.
[0030] More preferably, the reaction time in step 2) is selected from 12 to 24 hours.
[0031] Preferably, the mass ratio of the aldehyde-modified metal-organic framework to the thiol monomer is 1:1 to 5. More preferably, the mass ratio of the aldehyde-modified metal-organic framework to the thiol monomer is 1:1 to 2.
[0032] Preferably, an alkaline substance is added in step 2) to adjust the reaction.
[0033] Preferably, the alkaline substance is selected from hydroxides, carbonates, bicarbonates, or ammonium salts.
[0034] More preferably, the alkaline substance is selected from carbonates, such as sodium carbonate or potassium carbonate.
[0035] Preferably, the mass ratio of the aldehyde-modified metal-organic framework to the alkaline substance is 1:0.1~5; more preferably, the mass ratio of the aldehyde-modified metal-organic framework to the alkaline substance is 1:0.1~1.
[0036] Preferably, after the reaction in step 2) is completed, the product is post-processed.
[0037] Preferably, the post-processing includes filtration, separation, washing, and drying.
[0038] Preferably, the washing includes washing once or multiple times with DMF, ethanol and / or water.
[0039] Preferably, the step further includes the synthesis of a zirconium-based organometallic framework precursor, i.e., reacting an organic ligand with a zirconium salt.
[0040] Preferably, the organic ligand is selected from aminoterephthalic acid.
[0041] Preferably, the reaction is carried out in a solvent pool, the solvent being selected from one or more of DMF, 1,4-dioxane, or DMSO.
[0042] More preferably, the solvent is selected from DMF.
[0043] Preferably, the reaction temperature is selected from 50~240℃.
[0044] More preferably, the reaction temperature is selected from 100~120°C.
[0045] Preferably, the reaction time is selected from 12 to 36 hours.
[0046] More preferably, the reaction time is selected from 12 to 24 hours.
[0047] Preferably, a mineralizing agent is also added to the reaction system.
[0048] Preferably, the mineralizing agent is selected from acetic acid or concentrated hydrochloric acid.
[0049] More preferably, the mineralizing agent is selected from concentrated hydrochloric acid.
[0050] Preferably, the zirconium salt is selected from one or more of zirconium chloride, zirconium nitrate, zirconium sulfate, or zirconium citrate. More preferably, the zirconium salt is selected from zirconium chloride.
[0051] Preferably, the zirconium-based organometallic framework precursor is synthesized using a solvothermal method.
[0052] Preferably, after the reaction is complete, the product is post-processed.
[0053] Preferably, the post-processing includes filtration, separation, washing, and drying.
[0054] Preferably, the washing includes washing once or multiple times with DMF, ethanol and / or water.
[0055] Preferably, the method for synthesizing the thiol-modified MOF material of the present invention is prepared according to the following method: in Represents UiO-66-NH2, Represents UiO-66-CHO, The MOF material represents a thiol-modified material, and R-SH represents the thiol monomer described in this invention, namely trithiocyanate or 2,5-dimercapto-1,3,4-thiadiazole.
[0056] The third aspect of this invention provides the application of the thiol-modified MOF material described in the first aspect of this invention, or the MOF material prepared by the synthesis method of the thiol-modified MOF material described in the second aspect of this invention, in the adsorption of heavy metal ions.
[0057] Preferably, the heavy metal ion is lead ion.
[0058] Preferably, the lead ions are divalent.
[0059] Furthermore, the application is the adsorption of lead ions in an acidic aqueous phase.
[0060] Preferably, the aqueous phase system is one or a mixture of any two of pure water, tap water, or ordinary industrial wastewater.
[0061] Preferably, the pH range for adsorbing lead ions is pH=1~7.
[0062] More preferably, the pH range for adsorbing lead ions is pH=1~5.
[0063] Compared with the prior art, the present invention has the following beneficial effects: 1. By Figure 4 It can be deduced that the zirconium-based metal-organic framework with thiol groups loaded on its surface in this invention has a particle size of approximately 100 nm, belonging to nanomaterials; Figure 6 Combined with nitrogen adsorption-desorption testing, the BET specific surface area of the substrate UiO-66-NH2 was found to be as high as 1900 m². 2 / g, which is much higher than that of conventional materials, can be loaded with a large number of thiol groups, and can be used as an adsorbent to adsorb lead ions in the aqueous phase under acidic conditions.
[0064] 2. This invention uses an amino-containing carboxylic acid (such as aminoterephthalic acid) as a ligand, a zirconium salt (such as anhydrous zirconium chloride) as a metal salt, concentrated hydrochloric acid as a mineralizing agent, a mercapto-containing monomer (trithiocyanate or 2,5-dimercapto-1,3,4-thiadiazole) as a modifier, and an aldehyde (such as glutaraldehyde) as a linker. The mercapto-modified MOF can be obtained through a two-step modification using a solvothermal method. The method is simple, the reaction conditions are mild, no inert conditions or extreme high temperatures are required, and the cost of each component is relatively low, which has potential application value in the field of environmental protection. Attached Figure Description
[0065] Figure 1 The X-ray diffraction patterns of the series of metal-organic frameworks show good fit with the simulated data.
[0066] Figure 2 Infrared spectra of a series of metal-organic frameworks.
[0067] Figure 3 Thermogravimetric curves of a series of metal-organic frameworks.
[0068] Figure 4 (a), (b), and (c) are SEM images of Examples 1 and 2 and the MOF precursor, respectively.
[0069] Figure 5 The surface elemental distribution of the metal-organic framework after Pb adsorption in Example 1 was determined by SEM-Mapping.
[0070] Figure 6 The figures show the nitrogen adsorption-desorption curves of a series of metal-organic frameworks. (a), (b), and (c) represent the nitrogen adsorption-desorption curves of UiO-66-NH2, UiO-66-TCA, and UiO-66-MTD, respectively.
[0071] Figure 7 The adsorption amounts and adsorption isotherms of the thiol-modified metal-organic frameworks in Examples 1 and 2 are shown. Detailed Implementation
[0072] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.
[0073] The present invention will be further described below with reference to specific embodiments and examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments that do not specify specific conditions should preferably be performed according to the conditions indicated in the specific embodiments described above, and then may be performed under conventional conditions or as recommended by the manufacturer.
[0074] Unless otherwise stated, percentages and parts mentioned in this invention are weight percentages and weight parts.
[0075] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available products.
[0076] Unless otherwise specified, all temperature units in this application are Celsius (°C).
[0077] Nouns and terms The following are explanations or descriptions of the meanings of some relevant "nouns" and "terms" used in this invention to facilitate a better understanding of the invention. These explanations or descriptions apply to the entire text of this invention, both below and above. When references are made in this invention, the definitions of relevant terms, nouns, and phrases in the referenced documents are also cited; however, in case of conflict with the definitions in this invention, the definitions in this invention shall prevail. The conflict between the definitions in the referenced documents and the definitions in this invention does not affect the application of the cited components, substances, compositions, materials, systems, formulations, types, methods, equipment, etc., which shall be determined in the referenced documents.
[0078] MOF(s) is short for Metal-Organic Framework. It is a class of crystalline porous materials with a periodic network structure, formed by the self-assembly of inorganic metal centers (metal ions or metal clusters) and bridging organic ligands. MOF(s) are organic-inorganic hybrid materials, also known as coordination polymers. They differ from both inorganic porous materials and typical organic complexes, possessing both the rigidity of inorganic materials and the flexibility of organic materials. This gives them enormous development potential and an attractive future in modern materials research.
[0079] The term “about” can refer to a value or composition within an acceptable margin of error for a particular value or composition as determined by a person skilled in the art, depending in part on how the value or composition is measured or determined. For example, as used herein, the expression “about 100” includes all values between 99 and 101 (e.g., 99.1, 99.2, 99.3, 99.4, etc.).
[0080] The present invention adopts the following preferred embodiments: The zirconium-based organometallic framework precursor described in this invention is preferably UiO-66-NH2, and for ease of description and understanding, it is represented by the following structure. .
[0081] The preferred method for synthesizing the thiol-modified MOF material of the present invention is as follows: R-SH represents the thiol monomer described in this invention, such as trithiocyanate or 2,5-dimercapto-1,3,4-thiadiazole.
[0082] Represents UiO-66-CHO, This represents a mercapto-modified MOF material. Specific implementation examples: Example 1 2.6 g of anhydrous zirconium chloride and 2.05 g of aminoterephthalic acid were dissolved in 125 mL of DMF, and 2.5 mL of concentrated hydrochloric acid was added as a mineralizing agent. The mixture was heated to 120 °C and reacted for 24 h. After the reaction was completed, the product was filtered and separated. It was washed three times with N,N-dimethylformamide, 95% ethanol and purified water, dried, and named UiO-66-NH2.
[0084] Take 4g of UiO-66-NH2 and add it to 300mL of anhydrous ethanol. After dispersing it thoroughly, add 20mL of 50% glutaraldehyde aqueous solution, stir for 10min, and then reflux at 80℃ for 24h. After the reaction is complete, filter to separate the product, wash it repeatedly three times with 95% ethanol and deionized water, and dry it. The product is named UiO-66-CHO.
[0085] Take 1.2g UiO-66-CHO, 1.2g sodium carbonate, and 2.4g trithiocyanate and place them in a single-necked flask. Add 300ml DMF and stir thoroughly until completely dispersed. Heat to 80℃ and react for 24h. After the reaction is complete, filter to separate the product, wash repeatedly three times with DMF, 95% ethanol, and deionized water, and dry at 60℃ to obtain the product, named UiO-66-TCA.
[0086] Example 2 2.6 g of anhydrous zirconium chloride and 2.05 g of aminoterephthalic acid were dissolved in 125 mL of DMF, and 2.5 mL of concentrated hydrochloric acid was added as a mineralizing agent. The mixture was heated to 120 °C and reacted for 24 h. After the reaction was completed, the product was filtered and separated. It was washed three times with N,N-dimethylformamide, 95% ethanol and purified water, dried, and named UiO-66-NH2.
[0087] Take 4g of UiO-66-NH2 and add it to 300mL of anhydrous ethanol. After dispersing it thoroughly, add 20mL of 50% glutaraldehyde aqueous solution, stir for 10min, and then reflux at 80℃ for 24h. After the reaction is complete, filter to separate the product, wash it repeatedly three times with 95% ethanol and deionized water, and dry it. The product is named UiO-66-CHO.
[0088] Take 1.2g UiO-66-CHO, 1.2g sodium carbonate, and 2.4g 2,5-dimercapto-1,3,4-thiadiazole and place them in a single-necked flask. Add 300mL DMF and stir thoroughly until completely dispersed. Heat to 80℃ and react for 24h. After the reaction is complete, filter to separate the product, wash repeatedly three times with DMF, 95% ethanol, and deionized water, and dry at 60℃ to obtain the product, named UiO-66-MTD.
[0089] Application Example 1 Adsorption of Pb(II) by the product Prepare a 500 mg / L lead nitrate aqueous solution. Take 10 mL of the solution and add it to a glass screw-top bottle. Add 5 mg of the adsorbent prepared in Example 1 or 2. The mixed glass screw-top bottle was placed in a multi-stage water bath and stirred and adsorbed at 30°C for 12 hours under constant temperature conditions in the water bath. Take the mixed liquid and separate it using a needle filter. Use the filtrate to test the adsorption capacity. Disodium ethylenediaminetetraacetate was used as a chelating agent, acetic acid-sodium acetate solution was used as a buffer solution, and disodium xylenol orange was used as a buffer solution. The concentration of lead ions in the filtrate was determined by volumetric titration, and the adsorption capacity was calculated.
[0090] Calculations showed that the maximum adsorption capacity of Pb(II) in Example 1 was 920.11 mg / g, and the maximum adsorption capacity of Pb(II) in Example 2 was 464.90 mg / g (see [reference]). Figure 7 (and Table 1) Application Example 2 Determination of product adsorption isotherms In addition, the Langmuir, Freundlich, and Temkin models were used to fit the data. For Example 1, the R-squared values of the Langmuir, Freundlich, and Temkin isotherm models were... 2The values were 0.9961, 0.9899, and 0.9921, respectively; for Example 2, the R-values of the Langmuir, Freundlich, and Temkin isotherm models were... 2 The values are 0.9978, 0.9661, and 0.983 respectively (see...). Figure 7 (and Table 1). It is evident that the adsorption thermodynamics of Pb(II) by the two types of MOFs are more consistent with the Langmuir model, meaning that the metal ions are uniformly adsorbed through the supported active sites.
[0091] Table 1 Adsorption isotherm parameters of Examples 1 and 2 The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.
Claims
1. A mercapto-modified MOF material, characterized in that: It includes the following structure (I) (I), where Represents UiO-66; R represents .
2. The method for synthesizing a mercapto-modified MOF material according to claim 1, characterized in that: The process includes the following steps: 1) reacting a zirconium-based organometallic framework precursor with an aldehyde to obtain an aldehyde-modified metal-organic framework; 2) reacting the aldehyde-modified metal-organic framework with a thiol monomer to obtain the thiol-modified MOF material.
3. The method for synthesizing a thiol-modified MOF material according to claim 2, characterized in that: The zirconium-based organometallic framework precursor is UiO-66-NH2 The aldehyde is glutaraldehyde, and the aldehyde-modified metal-organic framework is UiO-66-CHO. The thiol monomer is trithiocyanate.
4. A method for synthesizing a thiol-modified MOF material according to claim 2 or 3, characterized in that: The solvent used in step 1) is selected from one or more of methanol, ethanol, acetone, THF or DMF; the reaction temperature is selected from 50~150℃; the reaction time is selected from 12~36h; the mass ratio of the zirconium-based organometallic framework precursor to the aldehyde is (1~5):(1~10).
5. The method for synthesizing a mercapto-modified MOF material according to claim 4, wherein the reaction temperature is selected from 50~80℃.
6. The method for synthesizing a thiol-modified MOF material according to claim 4, wherein the reaction time is selected from 12 to 24 hours.
7. The method for synthesizing a mercapto-modified MOF material according to claim 4, wherein the mass ratio of the zirconium-based organometallic framework precursor to the aldehyde is (4~5):(5~10).
8. A method for synthesizing a thiol-modified MOF material according to claim 2 or 3, characterized in that: The solvent used in step 2) is selected from one or more of DMF, 1,4-dioxane or DMSO; the reaction temperature is selected from 50~240℃; the reaction time is selected from 12~36h; and the mass ratio of the aldehyde-modified metal-organic framework to the thiol monomer is 1:1~5.
9. The method for synthesizing a mercapto-modified MOF material according to claim 8, wherein the reaction temperature is selected from 80~120℃.
10. The method for synthesizing a thiol-modified MOF material according to claim 8, wherein the reaction time is selected from 12 to 24 hours.
11. The method for synthesizing a thiol-modified MOF material according to claim 8, wherein the mass ratio of the aldehyde-modified metal-organic framework to the thiol monomer is selected from 1:1 to 2.
12. A method for synthesizing a thiol-modified MOF material according to claim 2 or 3, characterized in that: The step further includes the synthesis of a zirconium-based organometallic framework precursor, namely, reacting an organic ligand amino terephthalic acid with a zirconium salt; the solvent for the reaction is selected from one or more of DMF, 1,4-dioxane or DMSO; the reaction temperature is selected from 50~240℃; and the reaction time is selected from 12~36h.
13. The method for synthesizing a thiol-modified MOF material according to claim 12, wherein the reaction temperature is selected from 100~120℃.
14. The method for synthesizing a thiol-modified MOF material according to claim 12, wherein the reaction time is selected from 12 to 24 hours.
15. The method for synthesizing a thiol-modified MOF material according to claim 12, characterized in that: A mineralizing agent, selected from acetic acid or concentrated hydrochloric acid, was also added to the reaction system.
16. The method for synthesizing a mercapto-modified MOF material according to claim 12, characterized in that: The zirconium salt is selected from one or more of zirconium chloride, zirconium nitrate, zirconium sulfate, or zirconium citrate.
17. The application of the thiol-modified MOF material according to claim 1 in the adsorption of heavy metal ions.
18. The application of the thiol-modified MOF material according to claim 17 in the adsorption of heavy metal ions, characterized in that: The heavy metal ion is lead ion.
19. The application of the thiol-modified MOF material according to claim 18 in the adsorption of heavy metal ions, wherein the lead ion has a +2 valence.
Citation Information
Patent Citations
Thiol-functional metal-organic framework material as well as preparation and application thereof
CN109317104A
A modified zirconium-based organometallic framework adsorbent for adsorbing lead ions, its preparation method and application
CN110813244B